"I'm Afraid It's Going to be Awkward": Students' Perceived Barriers to Visiting Instructors During Office Hours - Mary Stairs Vaugh; Amy Schmisseur; Christie Kleinmann; Jason Stahl (Park University, 2024)
Research shows that students benefit from outside-of-class interaction with instructors (Guerrero & Rod, 2013; Pascarella & Terenzini, 2005) yet rarely take advantage of visiting faculty during office hours (Abdul-Wahab et al., 2019; Bippus et al., 2003; Griffin et al., 2014). We interviewed 39 students in six focus groups to learn more about why this is the case. Our transcribed focus group discussions revealed six barriers students experience interacting with faculty during office hours and six ways students perceive faculty mitigating the barriers. From these data, we note three implications for instructors as they understand and manage their interaction with students outside of class.